Step
*
1
of Lemma
Riemann-integral-rmul-const
1. a : ℝ
2. b : {b:ℝ| a ≤ b}
3. f : {f:[a, b] ⟶ℝ| ifun(f;[a, b])}
4. c : ℝ
⊢ ∫ c * (f x) dx on [a, b] = (c * ∫ f x dx on [a, b])
BY
{ (InstLemma `Riemann-sums-converge-to` [⌜a⌝;⌜b⌝]⋅ THENA Auto) }
1
1. a : ℝ
2. b : {b:ℝ| a ≤ b}
3. f : {f:[a, b] ⟶ℝ| ifun(f;[a, b])}
4. c : ℝ
5. ∀f:{f:[a, b] ⟶ℝ| ifun(f;[a, b])} . lim k→∞.Riemann-sum(λx.f[x];a;b;k + 1) = ∫ f[x] dx on [a, b]
⊢ ∫ c * (f x) dx on [a, b] = (c * ∫ f x dx on [a, b])
Latex:
Latex:
1. a : \mBbbR{}
2. b : \{b:\mBbbR{}| a \mleq{} b\}
3. f : \{f:[a, b] {}\mrightarrow{}\mBbbR{}| ifun(f;[a, b])\}
4. c : \mBbbR{}
\mvdash{} \mint{} c * (f x) dx on [a, b] = (c * \mint{} f x dx on [a, b])
By
Latex:
(InstLemma `Riemann-sums-converge-to` [\mkleeneopen{}a\mkleeneclose{};\mkleeneopen{}b\mkleeneclose{}]\mcdot{} THENA Auto)
Home
Index